# Limit by polar coordinates: $\frac{2x(1-\cos(x-y))}{x^2+y^2}$

I need to prove that: $$\lim_{(x,y)\to (0,0)}\frac{2x(1-\cos(x-y))}{x^2+y^2} = 0$$ I have tried using polar coordinates, but I'm not comfortable with my approach. What I did was saying: $$|f(\rho\cos\theta,\rho\sin\theta)| = \frac{2\cos\theta(1-\cos(\rho(\cos\theta-\sin\theta))}{\rho} \leq \frac{2(1-\cos(\sqrt{2}\rho))}{\rho}$$ and this last expression converges to $$0$$ when $$\rho$$ goes to $$0$$ uniformly in $$\theta$$. Is this correct? How can I do it better? I'm also looking for a way to solve this limit without using polar coordinates ( the easier, the better) . Any ideas?

• If you use L'Hospital's Rule on that last expression you'll be done. Commented Mar 11, 2019 at 15:25

The inequality you have written is wrong. Cosine is not an incerasing function so $$x\leq y$$ does not imply $$\cos\, x \leq \cos \, y$$. Instead, use the inequality $$1-\cos \theta \leq \frac {\theta^{2}} 2$$ valid for all real $$\theta$$. Proof of this inequality: $$1-\cos \theta -\frac {\theta^{2}} 2$$ vanishes at $$0$$ and its derivative is $$\sin\, \theta - \theta$$ which is negative for all $$\theta >0$$. Hence the inequality holds for all positive $$\theta$$. Since both sides are even functions the inequality holds for all $$\theta$$.

Use the half-angle formula $$1-\cos(x-y) = 2\sin^2\left(\frac{x-y}2\right) = 2\sin^2 \left(\frac{r(\cos\theta-\sin\theta)}{2}\right)$$

so

$$\left|\frac{2x(1-\cos(x-y))}{x^2+y^2}\right| = 4\left|\cos\theta\right| \frac1{r}\sin^2\left(\frac{r(\cos\theta-\sin\theta)}{2}\right) \le \frac4{r}\sin^2\left(\frac{r\sqrt2}{2}\right) \xrightarrow{r\to 0} 0$$

because $$\sin^2$$ is increasing on $$\left[0,\frac{\pi}2\right]$$.

• You probably also need that $\sin^2(r) \approx r^2$, since you have that factor $1/r$ to take care of. Commented Mar 11, 2019 at 15:24
• @ThomasAhle It follows from $\sin x \le x, \forall x \ge 0$ like this: $$\frac4r \sin^2\left(\frac{r\sqrt{2}}2\right) \le \frac4r \left(\frac{r\sqrt{2}}2\right)^2 = 2r \xrightarrow{r\to 0} 0$$ Commented Mar 11, 2019 at 15:54

Solution without the use of polar coordinates, as asked by OP at the end of their post.

Rewrite \begin{aligned}1-\cos(x-y)&=1-\cos x \cos y - \sin x \sin y \\ &=1-\cos x + \cos x (1-\cos y)- \sin x \sin y, \end{aligned} then \begin{aligned}\frac{2x(1-\cos(x-y))}{x^2+y^2}&= 2x\cdot \frac{1-\cos x}{x^2} \cdot\frac{x^2}{x^2+y^2}\\ &+ 2x\cos x \cdot \frac{1-\cos y}{y^2}\cdot\frac{y^2}{x^2+y^2}\\&- 2y\cdot \frac{\sin x}{x}\cdot\frac{\sin y}{y}\cdot\frac{x^2}{x^2+y^2}\end{aligned} From where is $$\lim_{(x,y)\to (0,0)}\frac{2x(1-\cos(x-y))}{x^2+y^2} = 0.$$